Relationship Between Shoulder Rotation Strength and Upper Extremity Functional Assessments in Collegiate Baseball Players - Andy Waldhelm; Jaclyn Aida; Jackson Boyd; Garrett Chandler; Matthew Demboski; Caroline Monson; Neil Schwarz (Journal of Functional Morphology and Kinesiology)
Background/Objectives: In overhead throwing sports such as baseball and softball, upper extremity injuries are prevalent at both collegiate and high school levels. Currently, there is no universal assessment protocol to identify athletes at risk for injury or to determine their readiness to return to sport. This study aimed to investigate the relationship between shoulder internal rotation (IR) and external rotation (ER) isometric strength in a throwing position and three upper extremity functional tests among collegiate baseball players. It was hypothesized that there would not be significant correlations between shoulder IR and ER peak isometric force and the following functional assessments: the Upper Quarter Y Balance Test (YBT-UQ), seated single-arm shot put, and Closed Kinematic Chain Upper Extremity Strength Test (CKCUEST). Methods: Forty healthy collegiate baseball players volunteered for the study. After completing a self-guided warm-up, participants performed bilateral isometric shoulder IR and ER strength tests at 90 degrees of shoulder abduction and elbow flexion, followed by the three functional tests in random order. Relationships were analyzed using Pearson’s correlation coefficients (r), with a significance level set at p < 0.05. Results: Correlations were generally low, ranging from r = 0.001 to r = 0.551. Significant correlations were observed between the CKCUEST and dominant IR strength (r = 0.345, p = 0.031), dominant ER strength (r = 0.407, p = 0.010), and non-dominant ER strength (r = 0.551, p < 0.001). Additionally, a significant correlation was found between the dominant ER/IR strength ratio and the dominant arm superolateral reach on the YBT-UQ (r = −0.352, p = 0.026). No significant correlations were identified between isometric shoulder strength and the single-arm shot put. Conclusions: Most correlations were low to moderate, and only significant correlations between shoulder rotation isometric strength and one direction of the YBT-UQ and the CKCUEST were observed. Thus, shoulder rotation strength in a position similar to the cocking phase of overhead throwing may be valuable for return-to-sport criteria and injury screening for overhead athletes. However, further research is needed to validate these findings.